2016
DOI: 10.1063/1.4955204
|View full text |Cite
|
Sign up to set email alerts
|

Transport mechanism through metal-cobaltite interfaces

Abstract: The resistive switching (RS) properties as a function of temperature were studied for Ag/La$_{1-x}$Sr$_x$CoO$_3$ (LSCO) interfaces. The LSCO is a fully-relaxed 100 nm film grown by metal organic deposition on a LaAlO$_3$ substrate. Both low and a high resistance states were set at room temperature and the temperature dependence of their current-voltage (IV) characteristics was mea- sured taking care to avoid a significant change of the resistance state. The obtained non-trivial IV curves of each state were wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…[28] In fact, this method has proven to be extremely useful in determining the presence of different transport mechanisms when more than one contributes to electric transport. [29][30][31] As shown in Fig. 4, despite the noise associated with the calculation of the derivative, it can be observed that γ follows a complex curve, indicating the presence of more than one conduction process.…”
Section: Resultsmentioning
confidence: 90%
“…[28] In fact, this method has proven to be extremely useful in determining the presence of different transport mechanisms when more than one contributes to electric transport. [29][30][31] As shown in Fig. 4, despite the noise associated with the calculation of the derivative, it can be observed that γ follows a complex curve, indicating the presence of more than one conduction process.…”
Section: Resultsmentioning
confidence: 90%
“…This figure points out the importance of performing IV measurements at different temperatures (see ref. [12]), as this can be a way to determine (or to check) the temperature dependence of microscopic parameters, like ǫ ′ (T) (from C) or φ B (from the temperature dependence of R P F ), as well as of other parameters, such as R 1 or R 2 , which can also be temperature dependent.…”
Section: The Pf Mechanism As Nl Elementmentioning
confidence: 99%
“…This phenomenon occurs in many materials and at different temperatures (from 4 to 400K). Examples are oxide materials with a regular crystallographic structure, such as: TiO 2 [3], NiO, Al 2 O 3 [4,5], or having a more complex perovskite structure: YBa 2 Cu 3 O 7-x [6][7][8][9], Bi 2 Sr 2 CaCu 2 O 8+δ [10], Pr 1-x Ca x MnO 3 [11], La 1-x Sr x CoO 3 [12], SrTiO 3 [13]. The latter also exhibit the properties of high-temperature superconductors (HTS).…”
Section: Introductionmentioning
confidence: 99%